Establishment of Sensory Evaluation Method for Wolfberry Tea and Exploration of the Main Characteristic Aroma Substances - Yuanchao LI; Qinji LI; Yuqiong GUO; Zhilong HAO; Shan JIN (Shipin gongye ke-ji)
To establish the sensory evaluation method for wolfberry tea made from wolfberry buds and leaves, sensory evaluation experiments were designed with multi-variables, including brewing time and tea amount, by using two brewing methods with covered bowl and column cup, respectively. Based on the physicochemical methods and gas chromatography mass spectrometry (GC-MS) technology, the difference of taste and aroma substances between buds and leaves of wolfberry tea, were analyzed, and the main characteristic aroma compounds of wolfberry tea were explored. Results showed that the column cup brewing method with 4 g tea and 2 min brewing time was more suitable for the sensory evaluation of wolfberry tea. Through the sensory evaluation, salty (cooked vegetable aroma) and sweet aroma were considered to be the main aroma characteristics of wolfberry tea. Through OPLS-DA analysis, nine characteristic aroma components of wolfberry tea were identified, including benzaldehyde, 3,5-octadien-2-one, 2,4-ditert-butylphenol, 6-methylhept-5-en-2-one, hexanal, trans-2-hexen-1-ol, isopinocarveol, 2,4-dimethyl benzaldehyde, and styrene. These nine aroma components could be the potential contributors to the salty (cooked vegetable aroma) aroma. This study can not only provide a reference for the sensory evaluation system establishment and grade classification of wolfberry tea, but also provide a theoretical basis for the study of the aroma quality of wolfberry tea.